Un messale i il suo sistema illustrativo. Contributo per la miniatura “Bari type” - Orofino, Giulia (ASPICE HUNC OPUS MIRUM: Festschrift on the occasion of Nikola Jakšić’s 70th birthday, 2020)
The following essay will examine a fragmentary missal whose constituent parts are currently held by various institutions throughout Switzerland. Until now the work has been almost entirely ignored in the world of art historiography, despite the fact that it represents an outstanding specimen, not only when considered from textual, codicological and palaeographical viewpoints, but above all on account of its gold embellished decorative apparatus. The work of a single hand, the apparatus is of high quality and shows striking illustrative originality. The information that can be inferred from the script (Beneventan, with clearly “Bari type” characters) and from the decorations (ornamental initials and marginal illustrations that highlight the structure of the text, thereby intensifying the power of the sacred words), suggest an attribution of the 18 surviving leaves to a leading scriptorium of the Terra di Bari and a dating to within the first half of the 11th century.